Sex, vaccination status, and comorbidities influence long COVID persistence - Trevon Fuller; Roxana Flores Mamani; Heloísa Ferreira Pinto Santos; Otávio Melo Espíndola; Lusiele Guaraldo; Carolina Lopes Melo; Michele Fernanda Borges Da Silva; Guilherme Amaral Calvet; Leonardo Soares Bastos; Marília Sá Carvalho; Patrícia Brasil (Elsevier, 2024)
Background: There is interest in the public health impact of Long COVID, defined as symptoms that persist or begin after SARS-CoV-2 infection. We aimed to identify demographic and clinical risk factors associated with Long COVID over time in an Upper Middle-Income Country (UMIC) and potential biomarkers predictive of symptom trajectory. Methods: Prospective cohort study of adults with mild SARS-COV-2 during the Omicron period. We tracked symptom persistence and IgG antibody titers against the spike S1 subunit. Results: Of 383 participants, 276 had confirmed SARS-CoV-2 infection. Long COVID persisted for ≥ two months in 21 % and ≥ 12 months in 5 %. The most common symptoms were fatigue, upper respiratory symptoms, and myalgia/arthralgia: 15 % had fatigue for ≥ one month, 10 % for ≥ two months, and 5 % ≥ three months. Upper respiratory symptoms lasted ≥ one month in 17 %, ≥ two months in 7 %, and ≥ three months in 3 %. Fully 9 % reported myalgia/arthralgia lasting ≥ one month, 6 % ≥ two months, and 4 % ≥ three months. Risk factors for symptom persistence included female sex, not being fully vaccinated, and comorbidities. Participants experiencing persistent fatigue had lower anti-S1 IgG titers. Conclusions: In this population, symptom persistence declined after the acute phase, but 5 % of participants did not fully recover. Even in a population that was almost fully vaccinated, women, individuals with comorbidities, and the few remaining people who were unvaccinated were at greater risk for Long COVID. Immunoglobulins may have utility as a biomarker of Long COVID fatigue in this population.